The Usefulness of Cell Phones for Crop Farmers in Selected Regions of Bangladesh - Mamun-ur-Rashid , Md; Karim , Md Masud; Islam , Md Muzahidul; Mobarak , Md Soad Bin (Asian Journal of Agriculture and Rural Development, 2019)
This research endeavours the usefulness of cell phones for crop farmers in selected region of Bangladesh. For adequate findings and to achieve its purpose, structured interview schedule was adopted to collect data from 281 randomly selected farmers and it was revealed that a little over 60% of them found cell phones very useful, while only 5.3% respondents found the cell phone as less useful. Based on average talk time hours spend in the last six months, top three sources of agricultural information were friends and relatives, distributors and middlemen, and farmers in advanced categories. The results of the ordered logit model showed that their usefulness was significantly determined by age, farm size, per month call charges, and experience in using cell phones. Higher call rates, lack of awareness and paucity of mobile-based information sources were major bottlenecks in using cell phones for agricultural information. The recommendations suggested therein lead to connecting farmers with reliable and rich information sources, use of MMS and SMS, voice call activities, providing subsidized SIM cards, and ultimately undertake widespread campaigns for training of aged farmers to persuade their interest towards the use of cell phones and mobile-based information sources.